Development and Validation of a Worktext in Statistics for Nursing Students - Cadorna, Edelyn Alicar; Cadorna, Erwin F. (JPAIR Multidisciplinary Research, 2009)
This study was conducted to develop and validate a Worktext in Statistics for Nursing Students. The topics covered in the worktext include basic concepts in statistics; collection and presentation of data; measures of central tendency; measures of dispersion; measures of position; probability; vital statistics; nature, scope and significance of demography, and fundamentals of inferential statistics. After the construction of the worktext, it was content validated by the Instructional Materials Development Committee (IMDC) of the university. Said worktext was evaluated in terms of content characteristics and instructional characteristics. The degree of agreement of the evaluators was likewise determined. Comments and suggestions of the evaluators in the improvement of the worktext were also solicited and incorporated. Findings of the study revealed that the developed worktext was rated excellent by the experts indicating that it is very much valid as an instructional material. Likewise, the experts were consistent in their evaluation of the worktext. As regards the pilot testing part of the study, no significant difference was found between the mean pretest scores of the experimental and control groups. However, the students exposed to the worktext (experimental group) had a significantly higher mean posttest score in Statistics than the those who did not use the worktext (control group). This is an indication that the students in the experimental group learned better than those in the control group.
Keywords: worktext; statistics performance; instructional material